Book Review: Book Title: They Eat Our Sweat: Transport Labor, Corruption, and Everyday Survival in Urban Nigeria. Author: Daniel E. Agbiboa, Publisher: Oxford University Press. Year of Publication: 2022. Number of Chapters: 6 Number of Pages: 266 - ADINOYI, Oyiza Rhoda (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
How do the tendrils of corruption insidiously operate in the quotidian experiences of informal urban transport workers and in what ways do the multiform nature of corruption blur the line between normalcy and aberration? How do these workers spatially comply, resist, and reclaim their right to the city? This book explores the musky line between survival and corruption in the context of Lagos informal transport sector, where corruption is not a far elite phenomenon but a subtle naturalised societal norm recognisable in its banal forms in the informal settings. The informal transport workers in urban Lagos driven by the exigency of economic hardship are caught in the corrupt nexus of formal and informal paratransit regulators, where they are cornered to comply and avoid “time wastage, unnecessary fine, detention, vehicle impoundment, and tire deflation” (p.105). The author, through urban ethnography, semiotic interpretation, and cross-national comparison, meticulously mines oral accounts, court cases, and ephemeral texts to profoundly aver that the informal transport sector spatially functions as a fertile ground for culprit-victim corruption where exploitative exchanges are normalised.